Incidencia de neumonía en pacientes con accidente cerebrovascular en el Hospital Instituto Ecuatoriano de Seguridad Social de Babahoyo. - Jiménez Toaza, Claudia Teresa (2020)
Acute stroke constitutes the first cause of death worldwide and the third cause of disability. Pneumonia results as a common complication when associated with stroke, occurring in 44% of patients in the most complicated situations. Facing this situation, health related professionals who work in the environment of the patient become a basic structure for preventing both mortality and disability. In the field of physiotherapy, those who work with stroke affected patients can become widely useful in the treatment of the patient with stroke associated pneumonia, both in primary prevention, avoiding pulmonary complications, or in secondary prevention doing an early and effective treatment. A bibliographic review was made to observe the role of the physiotherapist in the treatment of stroke associated pneumonia patients, as part of the multidisciplinary team, outstanding those interventions where physiotherapist become the professional in charge of such treatmen.